PENGARUH RETURN ON ASSET (ROA) RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR TAMBANG BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Nababan, Grevina Oktavia; Gori, Evitya; Naibaho, Ayu; Purba, Lenta Friska; Acai Sudirman (Journal Accounting International Mount Hope, 2024)
This research aims to determine the effect of Return on Assets (ROA), Return on equity (ROE), and Debt to Equity Ratio (DER) to stock price on Mining in the coal subsector companies listed in Indonesia Stock Exchange 2018-2021 period either partially or simultaneously. This research is an causality research.The population in this research are coal mining companies. The sampling selection used purposive sampling technique and obtained 80 research samples of financial statements of issuers. The data in this research was secondary data obtained from Indonesia Stock Exchange (BEI). The data analysis used was descriptive analysis followed by requirement test include normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Statistical methods used to multiple linier regression analysis.The result of the research shows that : (1) ROA has positive effect on stock price, with tcount -2,726 > ttable 1,66488 (2) ROE has positive effect on stock price, with tcount 3,992 > ttable 1,66488 (3) DER has positive effect to stock price with value tcount 3,554 > ttable 1,66488 (4) ROA, ROE, and DER simultaneously have positive to Stock Return with value Fcount 11,798 > Ftable 2,72.